Detection of Cowdria ruminantium by means of a DNA probe, pCS20 in infected bont ticks, Amblyomma hebraeum, the major vector of heartwater in southern Africa. - Yunker, C. E. (Cambridge University Press, 1993)
A DNA probe, pCS20, previously described for use in detection of Cowdria ruminantium infections in Amblyomma variegatum (the principal vector of heartwater) hybridized with C. ruminantium DNA in organs of laboratory-infected A. hebraeum adult ticks (the major southern African vector of heartwater). The probe hybridized with C. ruminantium DNA in 46/49 midguts from male ticks and 26/29 from females, thus indicating infection. Corresponding salivary glands were less heavily infected, but infections were more numerous in glands from males. Infection in ticks was confirmed by transmission of the disease to susceptible goats. The probe did not hybridize with DNA from uninfected ticks or with DNA from a spotted fever group rickettsia commonly associated with A. hebraeum in Zimbabwe. The C. ruminantium specific pCS20 DNA probe can be applied to determine accurately the infection rates in the two major vectors of heartwater and the risk of exposure of ruminants in endemic areas.